2017
DOI: 10.1002/hbm.23928
|View full text |Cite
|
Sign up to set email alerts
|

Functional reorganization of intra‐ and internetwork connectivity in major depressive disorder after electroconvulsive therapy

Abstract: Electroconvulsive therapy (ECT) is an effective and rapid treatment for major depressive disorder (MDD). However, the neurobiological underpinnings of ECT are still largely unknown. Recent studies have identified dysregulated brain networks in MDD. Therefore, we hypothesized that ECT may improve MDD symptoms through reorganizing these networks. To test this hypothesis, we used resting-state functional connectivity to investigate changes to the intra- and internetwork architecture of five reproducible resting-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 70 publications
8
64
0
Order By: Relevance
“…For example, RS-fMRI findings have implicated decreased functional connectivity between the posterior default mode network and the central executive network (predominantly in the dorsolateral/dorsomedial prefrontal cortex) (Mulders et al, 2015). As an important addition to this work, findings from our previous study suggest that ECT increases the connectivity between the default mode network and the central executive network (Wang et al, 2018). This has been validated by another study that revealed enhanced connectivity between the dorsolateral prefrontal cortex and posterior default mode network following ECT (Abbott et al, 2013).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…For example, RS-fMRI findings have implicated decreased functional connectivity between the posterior default mode network and the central executive network (predominantly in the dorsolateral/dorsomedial prefrontal cortex) (Mulders et al, 2015). As an important addition to this work, findings from our previous study suggest that ECT increases the connectivity between the default mode network and the central executive network (Wang et al, 2018). This has been validated by another study that revealed enhanced connectivity between the dorsolateral prefrontal cortex and posterior default mode network following ECT (Abbott et al, 2013).…”
supporting
confidence: 51%
“…Consequently, ALFF is usually thought to reflect local spontaneous neural activity at rest (Zang et al, 2007). As an important addition to this work, findings from our previous study suggest that ECT increases the connectivity between the default mode network and the central executive network (Wang et al, 2018). In addition to being a localized summary measure, ALFF potentially impacts on functional connectivity (Cole, Yang, Murray, Repovs, & Anticevic, 2016).…”
mentioning
confidence: 64%
“…To further exclude head motion effects, “scrubbing” was employed to eliminate the bad images captured before two time points and after one time points, which exceeded the pre‐set criteria (frame displacement: FD, FD < 0.5) for excessive motion. Because previous studies have shown that global mean signal regression can lead to spurious resting‐state functional correlations and false inferences on the group level inference (Wang et al, ; Wang et al, ; Wang et al, ), thus, the global mean signal was not regressed during the preprocessing in our current study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an enhanced feedforward cortical-subcortical connectivity from the fusiform face area to the amygdala was observed in MDD patients who underwent series ECT (Wang et al, 2017). Moreover, Wang et al (2018) demonstrated that ECT may contribute to enhanced interactions in the intra-and inter-networks in MDD patients that result in symptom alleviation. Employed with perfusion MRI, ECT contributed to hippocampal cerebral blood flow increases and declines in specific regions relevant to seizure physiology.…”
Section: Clinical Observation By Medical Imaging Programsmentioning
confidence: 91%
“…In short, according to the functional MRI studies mentioned above, ECT studies have brought renewed interest to the neuroplasticity of the brain, not only the hippocampus, but neural networks also showed more profound activity (Cao et al, 2018;Wang et al, 2018;Nuninga et al, 2019;Qiu et al, 2019).…”
Section: Clinical Observation By Medical Imaging Programsmentioning
confidence: 99%